Proving ground : the untold story of the six women who programmed the world's first modern computer - Kleiman, Kathy (Grand Central Publishing, Hachette Book Group, 2022)
"After the end of World War II, top-secret research continued across the United States as engineers and programmers rushed to complete their confidential assignments. Among them were six pioneering women, tasked with figuring out how to program the world's first general-purpose, programmable, all-electronic computer - a machine built to calculate a single ballistic trajectory in twenty seconds rather than forty hours by human hand - even though there were no instruction codes or programming languages in existence. But their story, never told to the reporters and scientists who thronged the huge computer after it became public, was lost. Kathy Kleiman, through meticulous research and vivid prose, brings these women back to life, and back into the historical record. For more than two decades, she met with four of the original six ENIAC Programmers, poured over documentation and images, and recorded extensive oral histories with the women about their work. She found stories that had been relegated and dismissed by even computer history experts, who had assumed the women in the old black-and-white pictures with ENIAC were nothing more than models. PROVING GROUND is a character-driven narrative that restores these women to their rightful place as technological revolutionaries. As the tech world continues to struggle with gender imbalance and its far-reaching consequences, the story of the ENIAC Programmers' groundbreaking work is more urgently necessary than ever before, and PROVING GROUND is the celebration they deserve"--